PREVENTION OF IDENTIFICATION OF VIRTUAL MACHINE ENVIRONMENT ON WINDOWS OPERATING SYSTEM IN VIRTUALBOX BY MALWARE WITH FILESYSTEM, PROCESS, AND WINDOWS MANAGEMENT INSTRUMENTATION MODIFICATION - Rifky Zulmeika, Annisa
Anti-virtual machine (anti-VM), a virtual environment detection technique used by malware, is one of many challenges for malware researchers to overcome. This technique is used by malware to evade analysis in virtual machine environments. Whereas a virtual machine (VM) is needed as a media of analyzing malware in observing its malicious behavior. With this technique, malware can change its behavior by being benign or stop its malicious activity so that researchers cannot perform analysis. To overcome this, we studied anti-VM techniques on malware and then built a protection method on the VM to avoid malware detection. Through this approach, the result is the fact that the malware tries to hide its presence by first checking the parameters that indicate the presence of the VM as a detection process. These parameters are termed as artifacts. Among the artifacts are filesystem, process, and WMI. In other words, the malware will operate as it shoulld be if it cannot find the artifact when it is run. There are different types of artifacts that malware detects depending on the hypervisor and operating system used. In this research, a system solution for preventing identification of registry artifacts, MAC addresses, filesystems, processes, and WMI on VirtualBox with Windows operating system is offered through modification. However, in this final project book, the modified system discussed only focuses on three artifacts, specifically filesystem, process, and WMI. The modified system was designed and implemented using a Powershell script which was then integrated in the form of an executable file. System testing is carried out using two anti-VM tools, those are sems and Pafish so that they can determine the effectiveness of the system created. The result states that the system has succeeded in modifying 21 types of filesystem, process, and WMI artifacts in total. From 21 artifacts, the system has succeeded in hiding 20 types of artifacts from anti detection by anti-VM tool. In addition, the system has been tested to be applicable to Windows 7 32-bit and Windows 10 64-bit.